Legislating instability : Adam Smith, free banking, and the financial crisis of 1772 - Goodspeed, Tyler Beck (Harvard University Press, 2016)
"From 1716 to 1845, the Scottish financial system functioned with no official central bank or lender of last resort, no public (or private) monopoly on currency issuance, no legal reserve requirements, and no formal limits on bank size. In support of previous research on Scottish "free banking," the author argues that this absence of legal restrictions on Scottish banking contributed to a proliferation of what Adam Smith derisively referred to as "beggarly bankers," which rendered the Scottish financial system both intensely competitive and remarkably resilient to a series of severe adverse shocks to the small developing economy. In particular, despite large speculative capital flows, a fixed exchange rate, and substantial external debt, Scotland's highly decentralized banking sector effectively mitigated the effects of two severe balance of payments crises arising from exogenous political shocks during the Seven Years' War. The author further argues that the introduction of regulations and legal restrictions into Scottish banking in 1765 was the result of aggressive political lobbying by the largest Scottish banks, and effectively raised barriers to entry and encouraged banking sector consolidation. While these results did not cause the severe financial crisis of 1772, they amplified the level of systemic risk in Scottish credit markets and increased the likelihood that portfolio losses in the event of an adverse economic shock would be transmitted to depositors and noteholders through disorderly bank runs, suspensions of payment, and institutional liquidation. Unlimited liability on the part of Scottish bank shareholders attenuated the effects of financial instability on the real economy."--Provided by publisher.